A liquid chromatography-high-resolution mass spectrometry method for separation and identification of hemoglobin variant subunits with mass shifts less than 1 Da - Ainslie Chen; Ryan M. Aquino; Hector A. Vidal; Carolyn V. Wong; Ruben Y. Luo (Journal of Mass Spectrometry and Advances in the Clinical Lab)
Background: Identification of hemoglobin (Hb) variants is valuable in clinical testing. A common issue with conventional methods for identifying Hb variants is their subpar ability to provide structural breakdowns of the variants. Reports have surfaced of high-resolution mass spectrometry (HR-MS) methods that improve on traditional methods; however, ambiguities may arise without separation of Hb subunits prior to HR-MS analysis. Methods: We report a liquid chromatography-high-resolution mass spectrometry (LC-HR-MS) method to separate several pairs of normal and variant Hb subunits with mass shifts of less than 1 Da and successfully identify them in intact-protein and top-down analyses. LC separation was facilitated by a C4 reversed-phase column. Results: Seven heterozygous Hb variant samples (Hb C with α-thalassemia trait, Hb E, Hb D-Punjab, Hb G-Accra, Hb G-Siriraj, Hb Tarrant, and Hb G-Waimanalo) were selected to demonstrate the LC separation of Hb variant and normal subunits with mass shifts of less than 1 Da. The analytes could be explicitly observed in the deconvoluted MS1 mass spectra. The top-down analysis matched the amino acid sequences of the correct Hb variant subunits. Conclusions: The LC-HR-MS method described can effectively separate and identify Hb subunits, especially when the variant subunits have mass deviations of less than 1 Da from their corresponding normal subunits. With further evaluation to prove the clinical utility, the HR-MS methods including CE-HR-MS have the potential to complement or partially replace conventional methods of Hb variant identification in clinical laboratories.